Incentivising community self-consumption in energy markets: Stable coalition formation using cooperative game theory - Khaled Abedrabboh (10063125) (2025)
This paper examines coalition stability among prosumers and consumers in a local energy community. Using cooperative game theory, we model how coalitions can minimise collective disutility by sharing distributed energy resources (DERs) and optimising battery energy storage system (BESS) operation schedules. For disutility allocation among coalition members, the center-of-gravity of imputation set value (CIS-value) is applied, ensuring equitability and computational feasibility. The analysis focuses on stability of coalition structures, where all possible players’ deviations are considered. A blocking mechanism is implemented, where deviations can be blocked by a coalition if one member is made worse off by the deviation. A case study involving ten players is presented, showing that stable coalitions lead to more effective outcomes in terms of cost, emissions, and demand peak reduction. These findings demonstrate that cooperative game theory with coalition stability can enhance community self-consumption (CSC) within local energy communities. Other Information Published in: Applied Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apenergy.2025.126508